Studi perilaku konsumsi obat pada masyarakat pesisir - Cinta Puteri Salsabilla Suratinoyo; Angela Fitriani Clementine Kalesaran; Grace Debbie Kandou (Holistik Jurnal Kesehatan, 2026)
Background: Inappropriate medication use remains a public health issue, as it can reduce treatment effectiveness and increase the risk of complications. Coastal communities possess unique characteristics regarding healthcare access and medication habits that can influence medication consumption behavior. Therefore, this study was conducted to describe medication consumption behavior among the coastal community of Manado Tua Island. Purpose: To describe the knowledge, attitudes, and practices of the coastal community regarding medication consumption. Method: This was a descriptive study using a cross-sectional approach. The research was conducted in Manado Tua II Village, Manado Tua Island, Bunaken Islands District, between September 2025 and January 2026. A sample of 83 respondents was selected using purposive sampling. Data were collected via a structured questionnaire measuring knowledge, attitudes, and practices related to medication consumption. Univariate data analysis was performed by presenting frequency distributions, percentages, and measures of central tendency. Results: The majority of respondents were female (81.9%). Descriptive analysis showed a median knowledge score of 8.0. Regarding attitudes, there was a score variance of 6.58 among respondents. Practice scores indicated that 50% of respondents fell within the 23–34 range, with a median score of 28. Conclusion: The coastal community demonstrated adequate knowledge, positive attitudes, and generally good practices regarding medication consumption. However, education on rational medication use still needs to be improved.   Keywords: Attitudes; Coastal Community; Knowledge; Medication Consumption; Practices.